Computation of supersonic flow over flying configurations - Nastase, Adriana
This high level aerospace reference book will be useful for undergraduate, and graduate students of engineering, applied mathematics and physics. The author provides solutions for three-dimensional compressible Navier-Stokes layer subsonic and supersonic flows. * Computational work and experimental results show the real world application of computational results * Easy computation and visualization of inviscid and viscous aerodynamis characteristics of flying configerations * Includes a fully optimized and integrated design for a proposed supersonic transport aircraft.